Rewiring the Epigenetic Networks in MLL-Rearranged Leukemias: Epigenetic Dysregulation and Pharmacological Interventions - Chan, Anthony K. N.; Chen, Chun-Wei (Frontiers in Cell and Developmental Biology, 2019)
Leukemias driven by chromosomal translocation of the mixed-lineage leukemia gene (MLL or KMT2A) are highly prevalent in pediatric oncology. The poor survival rate and lack of an effective targeted therapy for patients with MLL-rearranged (MLL-r) leukemias emphasize an urgent need for improved knowledge and novel therapeutic approaches for these malignancies. The resulting chimeric products of MLL gene rearrangements, i.e. MLL-fusion proteins (MLL-FPs), are capable of transforming hematopoietic stem/progenitor cells (HSPCs) into leukemic blasts. The ability of MLL-FPs to reprogram HSPCs toward leukemia requires the involvement of multiple chromatin effectors, including the histone 3 lysine 79 methyltransferase DOT1L, the chromatin epigenetic reader BRD4, and the super elongation complex. These epigenetic regulators constitute a complicated network that dictates maintenance of the leukemia program, and therefore represent an important cluster of therapeutic opportunities. In this review, we will discuss the role of MLL and its fusion partners in normal HSPCs and hematopoiesis, including the links between chromatin effectors, epigenetic landscapes, and leukemia development, and summarize current approaches to therapeutic targeting of MLL-r leukemias.